Malformação do esqueleto axial associado com cranioschisis, exencefalia e palatoschisis em neonato de cão - Relato de caso - Galvão, André Luiz Baptista [UNESP]; Léga, Elzylene; Pinto, Mildre Loraine; Raposo, Talita Mariana Morata [UNESP]; Da Costa, Paula Ferreira [UNESP]; Magalhães, Geórgia Modé [UNESP]; De Vasconcellos, Amanda Leal [UNESP]; Jark, Paulo César [UNESP] (My University, 2013)
The etiology of certain congenital anomalies is still unknown. Form anomalies caused by changes during tissue differentiation of the embryonic disc. Among the disturbances caused by the failure of fusion structures, include: cranioschisis, palatoschisis, cheiloschisis, spina bífida and Schistosomus reflexus. The case report aims to describe the occurrence of cranioschisis, exencephaly and palatoschisis in a neonate canine breed pinscher.
Axial skeletal malformations associated with cranioschisis, exencephaly and palatoschisis in a dog neonate - Case report
Keywords: Deformity; Fetal; Monsters